Descriptive And Diagnostic Analysis Models In Paulo Coelho's Novels "The Alchemist" And "Brida" (Journal of Namibian Studies : History Politics Culture, 2023)
"The Alchemist" and "Brida" by Paulo Coelho are two novels that explore themes of personal growth and self-discovery through the use of descriptive and diagnostic analysis models. These models are used to create rich and engaging narratives that draw readers in and allow them to connect with the characters and their journeys. Descriptive analysis is used in both novels to create vivid and detailed descriptions of the settings and characters. In "The Alchemist," the Andalusian countryside and the desert are described in detail, using sensory details to bring them to life. Similarly, in "Brida," the world of witchcraft is brought to life through the use of descriptive analysis, with Coelho using sensory details to create a mystical and magical atmosphere. The characters in both novels are also given detailed descriptions, allowing readers to form emotional connections with them and understand their motivations. Diagnostic analysis is used in both novels to explore deeper themes and ideas related to personal growth and self-discovery. In "The Alchemist”, the protagonist Santiago goes on a journey of self-discovery and learns valuable lessons about himself and the world around him. Through his experiences, he engages in self-reflection and grows as a person. Similarly, in "Brida", the protagonist engages in various spiritual practices and reflects on her past experiences to discover her true path in life. Both models work together to create narratives that engage readers on both an emotional and intellectual level. The descriptive analysis draws the reader into the world of the story, allowing them to visualize the settings and characters. The diagnostic analysis allows readers to explore deeper themes and ideas related to personal growth and self-discovery, creating a more meaningful and impactful reading experience. "The Alchemist" and "Brida" use descriptive and diagnostic analysis models to create engaging and thought-provoking narratives. Through their use of these models, Coelho explores themes of personal growth and self-discovery, creating stories that resonate with readers and leave a lasting impact.